Diseño de un plan estratégico de mercadeo y producción de la empresa procesadora de alimentos mercados Amelia (2018)
In this monograph has done a marketing and production strategic plan of the food processing company Mercados Amelia, this marketing and production strategic plan is developed due to problems that the company has at the moment to try to get and keep clients. To develop the marketing and production strategic plan is necessary addressing all issues relationated with the company and its environment, to do this it will start talking about main features and the current operation of the company together with a contextualization of the Colombia´s fruit and vegetable market, after that, a process map will be made with the effective processes of the company at the present time, later an analysis of the company will be made with respect to the market in which it is located and this will be done through the SWOT matrix, with the analysis of this information, the correct strategic plan of marketing and production will be proposed that can replace or correct the deficiencies observed in the SWOT matrix and finally an implementation and monitoring methodology will be proposed to ensure the correct and continuous use of the strategic marketing and production plan.